Uporaba UML-ja za modeliranje sestave geografskih informacijskih sistemov - Šumrada, Radoš (Geodetski vestnik, 1999)
The paper presents the basic characteristics of the industrial UML standard (Unified Modeling Language) developed by OMG (Object Management Group). The primary aim of UML is the unification of modeling techniques applied in software, information and related systems. What follows is the description and the possibilities of UML application in GIS technology for information system modeling. Further on, the paper gives an outline of the role and the importance of UML selection in the scope of the emerging ISO 15046 group information/Geomatics
Keywords: geodezija; geografski informacijski sistemi; standardi